Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the equation $m^3-4m^2+m+6=0$

Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
÷
2

e
π
ln
log
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$m=-1.1061,\:m=1.3561$

Step-by-step explanation

Problem to solve:

$m^3-4m^2+m+6=0$
1

Moving the term $6$ to the other side of the equation with opposite sign

$m^3-4m^2+m=0-6$
2

Subtract the values $0$ and $-6$

$m^3-4m^2+m=-6$

Unlock this step-by-step solution!

Answer

$m=-1.1061,\:m=1.3561$
$m^3-4m^2+m+6=0$

Main topic:

Equations

Used formulas:

1. See formulas

Time to solve it:

~ 0.51 seconds